(untitled) (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
This scientific work examines the artistic portrayal of the reality of the totalitarian era in Q. Matmuratov’s novel "Terbenbes," as well as the issue of artistic image and artistic psychologism in the work. In the course of analysis, the novel reveals the artistic interpretation of the socio-political situation and historical events of the late 19th and early 20th centuries. The work realistically depicts the life of the people of the Aral Sea region, including their fishing lifestyle. Through the character of the main character, Lepes Bay, the psychological characteristics, entrepreneurial qualities, and social position of the people of that era are depicted. It is also scientifically proven that the novel is based on historical sources and created on the basis of prototypes of real people.